Glycyrrhizic Acid Promotes Osteogenic Differentiation of Human Bone Marrow Stromal Cells by Activating the Wnt/β-Catenin Signaling Pathway - Bai, Jinwu; Xu, Jianxiang; Hang, Kai; Kuang, Zhihui; Ying, Li; Zhou, Chenwei; Ni, Licheng; Wang, Yibo; Xue, Deting (Frontiers in Pharmacology, 2021)
Glycyrrhizic acid (GA) is a major triterpene glycoside isolated from liquorice root that has been shown to inhibit osteoclastogenesis. However, there have been no reports regarding the effect of GA on osteogenic differentiation. Therefore, this study was performed to explore the effects and mechanism of action of GA on osteogenesis. A CCK-8 array was used to assess cell viability. The osteogenic capability was investigated by real-time quantitative PCR, western blotting and immunofluorescence analyses. ALP staining and ARS were used to evaluate ALP activity and mineralisation, respectively. GA-GelMA hydrogels were designed to verify the therapeutic effects of GA in vivo by radiographic analysis and histological evaluation. Our results show that GA had no significant influence on the viability or proliferation of human bone marrow stromal cells (hBMSCs). GA promoted osteogenic differentiation and enhanced calcium deposition. Furthermore, ratio of active β-catenin and total β-catenin protein increased after treatment with GA. Wnt/catenin signalling inhibitor partially attenuated the effects of GA on osteogenic differentiation. In a mouse femoral fracture model, GA-GelMA hydrogels accelerated bone healing. Our results show that GA promotes the osteogenic differentiation of hBMSCs by modulating the Wnt/β-catenin signalling pathway. GA-GelMA hydrogels promoted bone fracture healing. GA has potential as a cost-effective treatment of bone defects.